2020
DOI: 10.1021/acs.estlett.0c00090
|View full text |Cite
|
Sign up to set email alerts
|

Complex Mixtures of Chlorinated Paraffins Found in Hand Wipes of a Norwegian Cohort

Abstract: Up to 18000 ng of total chlorinated paraffins (CPs) was found in hand wipes of individual adult participants in a Norwegian cohort study ( n = 60), with a geometric mean (SD) value of 870 (2700) ng. The CPs covered a wide range of alkane chain lengths from C 7 to C 48 with variable chlorine substitution. Complex mixtures of very-short-chain (vSCCPs, C <10 ), short-chain (SCCPs, C 10–13 ), medium-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“… 68 Similarly, CPs were found to be the most abundant flame retardants in the hand wipes of the same cohort. 53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 68 Similarly, CPs were found to be the most abundant flame retardants in the hand wipes of the same cohort. 53 …”
Section: Resultsmentioning
confidence: 99%
“… 61 Quantification of S/M/LCCPs of all samples fulfilled the criterion of R 2 ≥ 0.50 ( Table S2 ), 56 which suggested a mean deviation of concentration less than 40%. 53 The results with R 2 < 0.5 were reported as tentative values. 48 For quantification of vSCCPs, the R 2 ranged from 0.16 to 0.99 (median: 0.72; Table S3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Exposure via this pathway is extremely difficult to evaluate because both compound migration from materials and dermal absorption rates must be considered. While absorption characteristics for CPs have not yet been determined, Yuan et al [51] developed a model for CP exposure via hands using the USEPA's Exposure Factors Handbook [52] and earlier ex vivo studies of halogenated flame retardant (HFR) uptake [53]. Based on CP measurements in hand wipes from 60 participants, the median daily exposure to SCCPs and MCCPs was estimated to be 3.6 and 11 ng/kg body weight via the skin of hands alone.…”
Section: Implications For Human Exposurementioning
confidence: 99%
“…We note that studies have shown that the current analytical standards often include chlorine substitution patterns that are not commonly present in technical mixtures. For example, triple-chlorine substitution at the terminal carbon atom (e.g., 1,1,1,3,9,10,10,10-C 10 Cl 7 ) is usually not found in technical mixtures and environmental samples 12 . A more distributed chlorination pattern (e.g., 2,5,6,9-C 10 Cl 4 , 2,3,4,5,6,7,8,9-C 10 Cl 8 ) may have higher relevance, although the availability of such standards is limited.…”
Section: Methodsmentioning
confidence: 99%